A INTERNALISASI NILAI ETIKA KITAB TAISIR AL-KHOLLAQ UNTUK MEMBENTUK KEPRIBADIAN SISWA DI MA AL-BAIRUNY SAMBONG DUKUH JOMBANG: INTERNALISASI NILAI ETIKA KITAB TAISIR AL-KHOLLAQ UNTUK MEMBENTUK KEPRIBADIAN SISWA DI MA AL-BAIRUNY SAMBONG DUKUH JOMBANG - Jannah, Miftahul; Inayatul Ilahiyah, Iva (Al Tadib : Jurnal Ilmu Pendidikan, 2023)
Abstract: Education is a necessity that must be owned by every nation. With education, the direction of life will be arranged. As for one of the very important education is a matter of ethics. As is the case in MA Al-Bairuny which carries out book-based learning that discusses ethics with one of the objectives being to shape the personality of its students. This study discusses the internalization of ethical values in the Al-Khollaq taisir book, the personality of students at MA Al-Bairuny Sambong Dukuh Jombang, and the formation of student personalities at MA Al-Bairuny Sambong Dukuh Jombang. This research uses a qualitative approach with a case study type of research. Data collected from observations and interviews were analyzed using data wetness checking techniques through the source triangulation method. The results of the research that has been done show that the internalization of ethical values in the Taisir Al-Khollaq book at MA Al-Bairuny is carried out through direct learning using the lecture method. In addition, the school also always conducts briefings on ethics education for its students. And also the efforts of the teachers in educating the personality of students at MA Al-Bairuny are very diverse because they come from different backgrounds. The purpose of this internalization is to shape the personality of the students, because it does not rule out that the personalities of students at MA Al-Bairuny are all good and perfect. This is precisely the responsibility of the school to be able to shape the personality of students to be good.